Selenium-Containing Protein From Selenium-Enriched Spirulina platensis Attenuates High Glucose-Induced Calcification of MOVAS Cells by Inhibiting ROS-Mediated DNA Damage and Regulating MAPK and PI3K/AKT Pathways - Lin, Cong; Zhang, Li-jun; Li, Bo; Zhang, Feng; Shen, Qing-rong; Kong, Guo-qing; Wang, Xiao-fan; Cui, Shou-hong; Dai, Rong; Cao, Wen-qiang; Zhang, Pu (Frontiers in Physiology, 2020)
Hyperglycemia is the main feature of diabetes and may increase the risk of vascular calcification (VC), which is an independent predictor for cardiovascular and cerebrovascular diseases (CCD). Selenium (Se) may decrease the risk of CCD, and previous studies confirmed that Se-containing protein from Se-enriched Spirulina platensis (Se-SP) exhibited novel antioxidant potential. However, the effect of Se-SP against VC has been not investigated. Herein, the protective effect and underlying mechanism of Se-SP against high glucose-induced calcification in mouse aortic vascular smooth muscle cells (MOVAS) were explored. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) results showed time-dependent uptake of Se-SP in MOVAS cells, which significantly inhibited high glucose-induced abnormal proliferation. Se-SP co-treatment also effectively attenuated high glucose-induced calcification of MOVAS cells, followed by decreased activity and expression of alkaline phosphatase (ALP). Further investigation revealed that Se-SP markedly prevented reactive oxygen species (ROS)-mediated DNA damage in glucose-treated MOVAS cells. ROS inhibition by glutathione (GSH) effectively inhibited high glucose-induced calcification, indicating that Se-SP could act as ROS inhibitor to inhibit high glucose-induced DNA damage and calcification. Moreover, Se-SP dramatically attenuated high glucose-induced dysfunction of mitogen-activated protein kinases (MAPKs) and phosphatidylinositol-3-kinase/AKT (PI3K/AKT) pathways. Se-SP after Se addition achieved enhanced potential in inhibiting high glucose-induced calcification, which validated that Se-SP as a new Se species could be a highly effective treatment for human CCD.